Cr2O3 nanoparticles boosting Cr–N–C for highly efficient electrocatalysis in acidic oxygen reduction reaction. (25th May 2021) - Jiang, Tao; Luan, Weiling; Turyanska, Lyudmila; Feng, Qi
Abstract: Transition metal–nitrogen–carbon (M–N–C) catalysts have attracted significant attention for catalyzing oxygen reduction reactions (ORR). In this study, a porous Cr2 O3 @Cr–N–C catalyst with a small amount of Cr2 O3 nanoparticles loaded on the surface of Cr–N4 –C nanomaterials was prepared using synergistic heat treatment (SHT) method with zeolite imidazole frameworks (ZIFs) as precursors. TEM and spherical aberration-corrected TEM results demonstrated the presence of hollow morphologies, Cr2 O3 nanoparticles and atomic-level Cr distribution in Cr2 O3 @Cr–N–C. XPS, XRD and XAFS analysis indicated the coexistence of Cr2 O3 nanoparticles and Cr–N4 sites which were believed to act as active centers for ORR. In 0.1 M HClO4, this material showed outstanding ORR catalytic activity with a half-wave potential of 0.78 V that was 40 mV higher than the traditional heat treatment derived Cr–N–C. It also revealed relatively low Tafel slope of 52.2 mV dec −1 ; 4-electron pathway; remarkable stability and long-term durability. The improved ORR performance is mainly attributed to the synergy between Cr–N4 active center and Cr2 O3 nanoparticle. The SHT strategy reported here provides a new route to prepare highly efficient non-precious metal M−N–C catalysts with greater ORR activity and stability in acidic environments. Graphical abstract: Image 1 Highlights: Cr2 O3 @Cr–N–C was prepared by a synergistic heat treatment method. Formation of Cr2 O3 nanoparticle and Cr–N4 sites are confirmed by TEM, XPS and XAFS. Cr2 O3 @Cr–N–C shows E1/2 = 0.78 V that is only 80 mV lower than Pt/C in 0.1 M HClO4 . Cr2 O3 @Cr–N–C has comparable ORR activity to M-N-C (M = Fe, Co, Mn, Mg) in acidic media.